2007
DOI: 10.1002/ijc.22609
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon profiles in ovarian serous carcinomas

Abstract: Ovarian serous carcinoma is the most common and lethal type of ovarian cancer and its molecular etiology remains poorly understood. As an ongoing effort to elucidate the pathogenesis of ovarian serous carcinomas, we assessed the DNA copy number changes in 33 high-grade serous carcinomas and 10 low-grade serous tumors by using a genome-wide technique, single nucleotide polymorphism array, performed on affinity-purified tumor cells from fresh surgical specimens. Compared to low-grade tumors, highgrade serous car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 28 publications
8
114
2
Order By: Relevance
“…10 -12 We have demonstrated that RSF1 is located in the ch11q13.5 region, which is frequently amplified in several types of carcinoma, including ovarian highgrade serous carcinoma. 10,13,14 As compared to other genes within the ch11q13.5 amplicon, RSF1 exhibited the highest correlation between DNA amplification and RNA copy number, and it was responsible for cell growth in the presence of chemotherapeutic agents in ovarian cancer tissues, 10,15 suggesting that RSF1 serves as the "driver" gene within the ch11q13.5 amplicon. RSF-1 overexpression was highly associated with the most aggressive type of ovarian cancer, high-grade serous carcinoma, and shorter overall survival.…”
mentioning
confidence: 99%
“…10 -12 We have demonstrated that RSF1 is located in the ch11q13.5 region, which is frequently amplified in several types of carcinoma, including ovarian highgrade serous carcinoma. 10,13,14 As compared to other genes within the ch11q13.5 amplicon, RSF1 exhibited the highest correlation between DNA amplification and RNA copy number, and it was responsible for cell growth in the presence of chemotherapeutic agents in ovarian cancer tissues, 10,15 suggesting that RSF1 serves as the "driver" gene within the ch11q13.5 amplicon. RSF-1 overexpression was highly associated with the most aggressive type of ovarian cancer, high-grade serous carcinoma, and shorter overall survival.…”
mentioning
confidence: 99%
“…The latter two have the advantage of providing an unbiased genome wide assessment of copy number variation and have been widely used to characterize the complex genomic alterations attributable to ovarian cancer and reveal it to be a heterogeneous group of diseases , Meinhold-Heerlein et al 2005, Nakayama et al 2007, Staebler et al 2002. Recent studies of the genomic alterations between invasive serous carcinomas and low grade or borderline serous tumors have identified dramatic differences in DNA copy number changes (MeinholdHeerlein et al 2005, Nakayama et al 2007, Staebler et al 2002. High-grade serous carcinomas uniformly exhibited more extensive DNA copy number variations than borderline tumors or low-grade serous carcinomas (Figure 2).…”
Section: Global Assessment Of Copy Number Variation In Ovarian Cancermentioning
confidence: 99%
“…DNA copy number changes are represented as pseudocolor gradients corresponding to the folds of increase (red boxes) and decrease (blue boxes), as compared to pooled normal samples. Reproduced with permission (Nakayama et al 2007).…”
Section: Global Assessment Of Copy Number Variation In Ovarian Cancermentioning
confidence: 99%
See 2 more Smart Citations